Cephalomedullary Nail Fixation of Intertrochanteric Femur Fractures: Are Two Proximal Screws Better Than One?. Issue 11 (November 2017) - Serrano, Rafael; Blair, James A.; Watson, David T.; Infante, Anthony F.; Shah, Anjan R.; Mir, Hassan R.; Maxson, Benjamin J.; Downes, Katheryne W.; Sanders, Roy W.
Abstract : Objectives: To analyze radiographic changes in intertrochanteric (IT) fracture alignment after treatment with either a single sliding lag screw or an integrated compressed and locked, dual screw, cephalomedullary nail construct. Design: Retrospective comparative study. Setting: Level 1 regional trauma center. Patients: 1004 OTA/AO 31A, 31B2.1 fractures treated with either a single screw cephalomedullary nail (Gamma 3) or an integrated dual screw cephalomedullary nail (InterTAN) between February 1, 2005, and June 30, 2013. Four hundred thirteen remained after exclusion criteria; 130 were treated with a single screw device (79 stable and 51 unstable), and 283 with an integrated dual screw device (155 stable and 128 unstable). Intervention: Cephalomedullary nail insertion. Outcome Measures: Radiographic analysis included fracture pattern, fracture reduction, neck-shaft angle (NSA), and femoral neck shortening (FNS) differences at 3, 6, and 12 months. Measurements were normalized using known lag screw dimensions, digitally corrected for magnification. Rotation between x-rays was controlled using a ratio of known to measured dimensions. The Mann–Whitney U test was used for statistical analysis. Results: The single screw device resulted in 2.5 times more varus collapse (NSA) and 2 times more FNS over 1 year, as compared to the locked, integrated dual screw device, regardless of stability ( P < 0.001). NSA and FNS changes were greater for both devices in unstable fracture patterns, but significantly less movement occurred with the dual screw device ( P < 0.001). Conclusions: A cephalomedullary nail with 2 integrated proximal screws that can be compressed and then locked seems to maintain initial IT fracture reduction and subsequent position over time, with less varus collapse and less shortening than a single screw device. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.